2020
DOI: 10.1371/journal.pone.0229903
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM-independent isolation of circulating tumor cells with epithelial-to-mesenchymal transition and cancer stem cell phenotypes using ApoStream® in patients with breast cancer treated with primary systemic therapy

Abstract: Background Tumor cells with a mesenchymal phenotype and/or cancer stem-like cells (CSCs) are known to contribute to metastasis and drug resistance. Circulating tumor cells (CTCs) undergoing epithelial-mesenchymal transition (EMT) and CTCs reflecting a dedifferentiated CSC phenotype may not be detected using only an anti-EpCAM antibody to capture them. We used an antibody-independent CTC enrichment platform, ApoStream ® , which does not rely on any antibody, including anti-EpCAM, to capture EMT-and CSC-CTCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…They reported that the recovery rate was over 70% and viability was more than 97%. Recently reported studies have verified the ability to isolate CTCs from clinical samples using the ApoStream™ system [222,223].…”
Section: Separation Of Cellsmentioning
confidence: 99%
“…They reported that the recovery rate was over 70% and viability was more than 97%. Recently reported studies have verified the ability to isolate CTCs from clinical samples using the ApoStream™ system [222,223].…”
Section: Separation Of Cellsmentioning
confidence: 99%
“…This is advantageous as it is label free so separates cells independently of EpCAM expression and is highly specific, however expensive. The ApoStream technology (ApoCell) couples dielectrophoresis (DEP) with field-flow assist for the isolation of CTCs [ 126 ]. The device requires an initial Ficoll separation step to isolate PBMCs which are then processed using the device.…”
Section: Dielectrophoresismentioning
confidence: 99%
“…DEP is an epCAM independent, label-free enrichment system, separating rare cells simply on the basis of their specific electrical properties [ 13 ]. The technique is capable of isolating all types of solid tumour-related immortalized cells from the NCI-60 panel [ 24 ], and more recently to co-collect, together with CTCs, also stem-like cells (CSCs) and mesenchymal-like cells (EMT-CTCs) [ 50 ].…”
Section: The Role Of Dep For Ctc Detection In Prostate Cancermentioning
confidence: 99%
“…The most advanced DACS system, Apostream™ (Precision Medicine Group, LLC), is based on a complex continuous field-flow DEP fractionation schema (FFF-DEP) [ 51 ]. The system was successfully tested for different solid tumours to capture epithelial-like CTCs as well as mesenchymal- and stem-like CTCs [ 50 , 51 ]. The main limit of ApoStream™, as for similar DEP-based sorting systems, is the use of planar, interdigitated electrode configurations causing exponentially decaying DEP forces, which limits the size of the sorting volume on which the DEP forces can act efficiently and reduces cell throughput.…”
Section: The Role Of Dep For Ctc Detection In Prostate Cancermentioning
confidence: 99%